A Workshop on Scientific Journal Management Preparation and Publication of Scientific Works - Tjipto Djuhartono; Prasetio Ariwibowo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
This Community Service (PKM) aims to add new insights and knowledge for all supporting lecturers for Pancasila courses at Indraprasta University PGRI Jakarta regarding the importance of writing scientific papers, techniques and procedures for writing scientific publication articles, as well as concepts and techniques for writing scientific papers. publishing articles in national scientific journals, to managing Scientific Publication Journals. The community service methods used are training, workshops, and mentoring. The targets of this activity are all supporting lecturers for Pancasila and Citizenship courses at PGRI Indraprasta University as well as the Editorial Board of the Pancasila Journal and the Executive Board of the Center for Pancasila Studies at Indraprasta University, PGRI Jakarta (Unindra). The results of this training show good progress regarding the governance of the Jagadditha Journal: Journal of Diversity and National Insights, starting from improving OJS website services, having standard templates, focusing on discussion science, but not having national to international indexes such as the Digital Object Identifier (DOI). , Copernicus , Scopus, Directory of Open Access Journal (DOAJ), Morraref, Portal Garuda, Arjuna, to Sinta DIKTI.